Stratigraphic and Spatial Extent of HALIP Magmatism in Central Spitsbergen. (26th November 2022) - Senger, Kim; Galland, Olivier
Abstract: Rapid extensive magmatism may have a profound effect on global climate by liberating and releasing greenhouse gases to the atmosphere through contact metamorphism of lithologically heterogeneous host rocks and degassing of magma and associated lava flows. The high Arctic Archipelago of Svalbard offers accessible, superbly exposed outcrops revealing Early Cretaceous magmatism associated with the High Arctic Large Igneous Province (HALIP). In this contribution, we investigate the onshore‐offshore intrusive complex of central Spitsbergen formed due to HALIP activity, that is, the Diabasodden Suite. This is the most "data‐rich" part of Svalbard due to past petroleum exploration and research drilling. In this area, the predominantly dolerite intrusions are emplaced in a range of host rocks ranging from Permian carbonate‐dominated successions to organic‐rich shale‐dominated successions of Middle Triassic and Late Jurassic‐Early Cretaceous age. Two hundred sixty five individual igneous intrusions, covering 72 km 2, are exposed onshore in the study area. This equates to approximately 0.14–2.5 km 3 of emplaced magma. In addition, subsurface characterization using borehole, seismic and magnetic data indicates that an area of additional ca. 3, 000 km 2 is affected by magmatism (magma volume 3.2–195.2 km 3 ). Wireline logs in boreholes characterize both intrusions and associated aureoles. Aureoles with very low resistivity indicate occurrence of organic‐rich shales suggesting past fluid circulation and de‐gassing. This study forms the foundation for quantifying HALIP‐related magmatism in the data‐poorer parts of Svalbard, and other circum‐Arctic basins. Plain Language Summary: Volcanic eruptions are known to influence global climate today. In the past, even greater volcanic eruptions have happened than we know today, and some of these likely caused major global climatic shifts and contributed to mass extinctions. Volcanic eruptions are fed by a complex of sub‐surface magma pathways. If magma in such "plumbing systems" does not reach the Earth's surface, it will solidify horizontally (as sills) or vertically (as dykes). Together dykes and sills form an igneous complex that heats up the surrounding rocks and may cause the release of gas during this process. If this happens relatively near to the surface, this gas may escape to the atmosphere and contribute to global climate change. The key variables that control the extent of climate effects include the emplacement depth, the spatial extent of the magmatism and the lithology of the host rocks. In this paper, we examine the igneous complex of dykes and sills in Spitsbergen in the high Arctic. We use borehole, seismic and field data to calculate how much magma was emplaced in this area and discuss whether it may have contributed to global climate change approximately 125 million years ago. Key Points: Igneous intrusions are well exposed in central Spitsbergen across a range of host rocks Two‐hundred sixty five intrusions cover 72 km 2 of the onshore part, and a further 3, 000 km 2 of intrusions are characterized by geophysical data Igneous intrusions and associated aureoles are characterized by wireline data